1992
DOI: 10.22358/jafs/69896/1992
|View full text |Cite
|
Sign up to set email alerts
|

The chemical composition of different types and varieties of pea and the digestion of their protein in pigs

Abstract: Six varieties of white-flowered and three varieties of coloured-ftowered peas were analysed for content of nutrients and some antinutritional factors. In a trial on cannulated pigs, ileal and fala) digestibility of protein and amino acids wcre estimated. The coloured-flowered varieties of pea contained significantly more NDF (P <0,051, Klason lignin and tannins (P <0.01) Chan the white-flowered ones. The trypsin inhibitor activity ranged widety in both white-and coloured-flowered peas. Methionine, cystine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
32
2
5

Year Published

1993
1993
2004
2004

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 6 publications
18
32
2
5
Order By: Relevance
“…The negative relationships between TIA and ileal digestibility of protein or amino acids in feed pea samples were in agreement with previous reports (Bengala Freire et al 1991;Huisman et al 1992). Gdala et al (1992) also found a negative but non-significant relationship between TIA ileal protein or amino acid digestibility in peas. Fan , *, ** P < 0.10, P < 0.05 and P < 0.01, respectively.…”
supporting
confidence: 92%
“…The negative relationships between TIA and ileal digestibility of protein or amino acids in feed pea samples were in agreement with previous reports (Bengala Freire et al 1991;Huisman et al 1992). Gdala et al (1992) also found a negative but non-significant relationship between TIA ileal protein or amino acid digestibility in peas. Fan , *, ** P < 0.10, P < 0.05 and P < 0.01, respectively.…”
supporting
confidence: 92%
“…Several studies showed distinct differences in apparent ileal amino acid digestibility between different feedstuffs (Zebrowska et al, 1978;Buraczewska et al, 1987) and between the same kind of feedstuff (Gdala et al, 1992). A mathematical study showed that a large part of the variation in apparent ileal digestibility between amino acids could be explained by factors in the mathematical model (van Leeuwen et al, 1993a).…”
Section: Discussionmentioning
confidence: 99%
“…Gdala et al (1992) studied the relationship between CP digestibility and amino acid digestibility in peas. They concluded that the degree of accuracy to predict Met and Cys was much lower in comparison to the relationship found for Lys and Thr.…”
Section: Low Digestibility Of a Particular Amino Acid In A Particularmentioning
confidence: 99%
“…In experiments on growing pigs, Gdala et al (1992) found that ileal digestibility of protein of different pea cultivars (10 cultivars were compared) was significantly affected by NDF content. Also Fan and Sauer (1999) recently showed that the ileal digestibility values of the majority of the indispensable amino acids were negatively correlated with the NDF content in pea samples that originated from six cultures located in different places in Canada.…”
Section: Grain Legumesmentioning
confidence: 99%